(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2019)
This article presents the main characteristics and contours of the fundamental right to freedom of assembly in the Brazilian constitutional law questioning the existence of material limits to the exercise of this right. It deals with the history of the judicial precedents of the Federal Supreme Court on the subject. It analyzes the concepts of freedom and the theories about the restrictions to fundamental rights to propose a system that approximates the freedom of assembly of the full exercise of a democracy with plural manifestations of thought.